Non-Inverting Cascaded Bidirectional Buck-Boost DC-DC Converter with Average Current Mode Control for Lithium-Ion Battery Charger - Heri Suryoatmojo; Indra Anugrah Pratama; Soedibyo . (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
In order to develop renewable energy, it also needs to enhance the developing of supporting elements. For example, lithium-ion batteries as a component of energy storage. Lithium-ion batteries (Li-ion) have been chosen as energy storage devices for portable equipment, unmanned Aerial Vehicle (UAV) and grid storage systems. But there is a problem such as the process of charging the battery for UAV. Conventional converters used in those chargers have disadvantages such as limited power, lower voltage gain and also high current stress. Therefore, such converters are not efficient to be used for charging the battery. This paper proposes a cascaded bidirectional buck-boost converter for charging the battery. This converter can be operated bidirectional and have better rated power and higher voltage gain. Also, this topology has the same polarity with the input. From the test results, the converter can work in either forward or backward power flow. This converter is working in both buck or boost mode and has an efficiency of 83% in buck mode and 81% for boost mode. The charging process is about 83 minutes until SOC approximately 90 – 95.Keywords: battery charger, cascaded bidirectional buck – boost converter, constant current, li-ion introduction.